Strategy to Accelerate Sustainable Development in the Health Field in Bengkulu Province - Tajri Fauzan; Sigit Nugroho; Izharudin Izharudin (Jurnal Indonesia Sosial Teknologi, 2024)
This research aims to determine a strategy to accelerate the reduction of maternal mortality, infant mortality and stunting and to describe the acceleration of sustainable health development in Bengkulu Province. This research was designed as descriptive research with a correlational investigation and intervention study; namely, the research wanted to find significant variables related to the problem with minimum intervention. The sample in this study used a clustering technique (Cluster Random Sampling), using primary and secondary data. Primary data in this research uses a questionnaire. Meanwhile, the collected data will be tested using validity and reliability tests on research instruments. Meanwhile, to achieve the objectives of this research, data analysis will be carried out using the SWOT test. The research results found that strategies to accelerate the reduction of maternal mortality can be carried out by providing training or education to health cadres, adding skilled health workers, providing supporting facilities related to accelerated access to health services, providing education about the benefits of nutritious and balanced food to improve health. Meanwhile, the strategy to accelerate the reduction in child mortality is to assist in processing drinking water suitable for consumption, provide fast access to services with a community pick-up program, and create a health service program with early detection of diseases in pregnant women. Meanwhile, strategies to accelerate the reduction in stunting rates include providing assistance to treat stunting, providing education about nutritious and balanced food, and health service programs with early disease detection in expectant mothers. There are still many shortcomings; it is recommended that further researchers add research indicators to the variables studied and use the AHP and FGD analysis methods.